2015
DOI: 10.1039/c4ob02441a
|View full text |Cite
|
Sign up to set email alerts
|

Tandem catalytic oxidative deacetylation of acetoacetic esters and heteroaromatic cyclizations

Abstract: One pot syntheses of furan, thiophene, and pyrrole were accomplished by oxidative deacetylation using Mn(III)/Co(II) catalysts and the Paal-Knorr reaction from 1,5-dicarbonyl compounds, which are prepared from the conjugate addition of ethyl acetoacetate to α,β-unsaturated carbonyl compounds. The oxidative deacetylation and reductive cyclization of β-ketoesters derived from ethyl acetoacetate and o-nitrobenzyl bromides efficiently produced diversely substituted indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…HCl in acetic anhydride at 60 °C for 2 h to produce parabis(phenylfuryl)benzene 7a in 32% yield. 11 para-Bis(phenylthiophenyl)benzene 7a-s (the corresponding thiophene analogue), on the other hand, was obtained in 93% yield upon treatment with Lawesson's reagent at 60 °C for 2 h. 12 Paal-Knorr furan formation from bis-(1,4-dicarbonyl)compound 5d with para-benzenesulfonyloxy substituent required higher temperature at 110 °C in toluene for 10 h with p-TsOH to produce 7d in 25% yield. para-Bis(phenylfuryl)benzene 7e with parahydroxy substituent was then obtained in 50% yield by deprotection of the benzenesulfonyl group with t-BuOK in toluene at 70 °C for 30 min.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…HCl in acetic anhydride at 60 °C for 2 h to produce parabis(phenylfuryl)benzene 7a in 32% yield. 11 para-Bis(phenylthiophenyl)benzene 7a-s (the corresponding thiophene analogue), on the other hand, was obtained in 93% yield upon treatment with Lawesson's reagent at 60 °C for 2 h. 12 Paal-Knorr furan formation from bis-(1,4-dicarbonyl)compound 5d with para-benzenesulfonyloxy substituent required higher temperature at 110 °C in toluene for 10 h with p-TsOH to produce 7d in 25% yield. para-Bis(phenylfuryl)benzene 7e with parahydroxy substituent was then obtained in 50% yield by deprotection of the benzenesulfonyl group with t-BuOK in toluene at 70 °C for 30 min.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…We have now demonstrated that 1,4dicarbonyl compound 14 can be obtained in 94% yield by Mn(OAc) 3 /CoCl 2 -catalyzed oxidative deacetylation of 1,5-dicarbonyl compound 13, which can be easily prepared by the conjugate addition of readily available ethyl acetoacetate to methyl vinyl ketone 12. 11 It was thus envisioned that this sequence of reactions would yield diverse 1,4-dicarbonyl compounds containing a chalcophene moiety when it is applied to the conjugated unsaturated carbonyl compounds of chalcophenes, which would eventually lead to 2,2′-bichalcophenes.…”
Section: Syn Thesismentioning
confidence: 99%
“…15 Many others then modied the above original methods for the syntheses of various pyrrole compounds. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Transformation of D-glucose as sustainable biomass into 5hydroxymethyl-2-furfural (5-HMF) as a value-added platform chemical has been well documented in the literature in recent years. [34][35][36] Utilization of reducing sugars for the preparation of pyrroles would also be benecial and providential.…”
Section: Introductionmentioning
confidence: 99%